GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 718068772 species occurrences available in GBIF matching the query: All data. The dataset includes 718068772 records from 15769 constituent datasets: 2 records from Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007) (Eutardigrada; Macrobiotidea), with the first molecular data for the genus. 11897 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 253199 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 288 records from Estudio de la distribución geográfica de Peromyscus ochraventer y análisis de su variabilidad cromosómica. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 93 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 3633 records from Bioimages. 2 records from Shewanella marisflavi sp. nov. and Shewanella aquimarina sp. nov., slightly halophilic organisms isolated from sea water of the Yellow Sea in Korea. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 57 records from T-RFLP Bacteria 2008 RNA ProFIL. 5 records from A new species and new record of deep-sea scale-worms (Polynoidae: Polychaeta) from the Okinawa Trough and the South China Sea. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 1 records from Arthropoden aus südostalpinen Höhlen.. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 116410 records from Naturalis Biodiversity Center (NL) - Crustacea. 1 records from The rare deep-living hyperiid amphipod Megalanceoloides remipes (Barnard, 1932): complementary description and symbiosis. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 6 records from Hemichordata collection of National Museum of Nature and Science. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 8934 records from El género Bursera en México. Parte II. 90 records from A taxonomic revision of the genus Diplonevra Lioy (Diptera: Phoridae) from China. 15300 records from Base de datos de colecciones de maíces nativos, teocintles y Tripsacum de México. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 8 records from Galeus corriganae sp. nov., a new species of deepwater catshark (Carcharhiniformes: Pentanchidae) from Papua New Guinea. 5549 records from Diplopoda (NSMK-DI). 59335 records from USGS South Florida Fish and Invertebrate Assessment Network Crustaceans. 97 records from DMNH Eggs. 291 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Huevos (MFA-ZV-Or-Hu). 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 14122 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 1348 records from Inventory of Wari maro forest (Benin). 10703 records from Evaluación estacional de la fauna ictiológica, malacológica y flora ficológica de la Reserva de la Biósfera El Vizcaino, BCS, Fase I: Laguna Ojo de Liebre. 1490 records from A comprehensive checklist of earthworm species and subspecies from Vietnam (Annelida: Clitellata: Oligochaeta: Almidae, Eudrilidae, Glossoscolecidae, Lumbricidae, Megascolecidae, Moniligastridae, Ocnerodrilidae, Octochaetidae). 35 records from Zanobatus maculatus, a new species of panray from the Gulf of Guinea, eastern central Atlantic (Elasmobranchii: Batoidea: Zanobatidae). 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 398 records from Tsetse flies of East Africa update. 31917 records from Mollusca of Costa Rica (INBio). 8857 records from Artròpodes d'Andorra. 2 records from A new legskate, Sinobatis andamanensis (Rajiformes: Anacanthobatidae), from the Andaman Sea (northeastern Indian Ocean). 375 records from Phthiraptera. 173530 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 58475 records from Oregon State University Herpetological Collection. 8 records from Ortopthera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 18053 records from BLS Rare and Threatened Lichen Records: Wales. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 11 records from Redescription of the rare and endangered Broadfin Shark Lamiopsis temminckii (Müller & Henle, 1839) (Carcharhiniformes: Carcharhinidae) from the northeastern Arabian Sea. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 920 records from Annotated list of observed birds in W and Pendjari Reserves in Benin, February 2010. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 2 records from Cathorops festae (Boulenger 1898) (Siluriformes; Ariidae), a valid species from Ecuador and Peru. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 238546 records from Merseyside BioBank (unverified). 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 233 records from NBMP Woodland Survey. 123 records from Bryozoa of the British Isles. 814 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 3105 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 14 records from Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 2419 records from Invasión de Pinus spp y la conservación de la diversidad florística en Los Altos de Chiapas, México. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 29 records from Sulawesi Onthophagus: seven new species in select groups (Coleoptera: Scarabaeidae: Scarabaeinae). 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 13089 records from Ghent University - Zoology Museum - Vertebrate collection. 10730 records from Specimens of lichen herbarium KPABG. 336 records from Macroarthropods, Isua 2013, Greenland. 162205 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 815 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 5 records from Arthropoden aus südostalpinen Höhlen.. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 839 records from Asociación de cactáceas con arbustos en el desierto costero de Topolobampo, Sinaloa. 22 records from Taxonomic review of the genus Zethus Fabricius (Hymenoptera: Vespidae: Eumeninae) from Vietnam with descriptions of four new species. 258 records from The Glyptothorax of Sundaland: a revisionary study (Teleostei: Sisoridae). 215 records from The Diptera Site. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 4092 records from Ross Sea Biodiversity Survey 2004 (BioRoss). 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10072 records from Guadeloupe_Herbier. 28385 records from Plan de vertebrados de la Patagonia. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 2789906 records from International Barcode of Life project (iBOL). 14865 records from SUI Vertebrate Collection. 584 records from Florida Keys Reef Visual Census 1998. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 3 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 79 records from Complete list of isolated phyllosphere Methylobacterium strains. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 6 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 33 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 12019 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ameghino National Collection (MACNA). 4872 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 1189 records from Saproxylic insects caught in window traps and hatched from polypores in small and large old forests in southern Norway. 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 1 records from Nothrus spinifer. 914 records from European Pear Rust (Gymnosporangium sabinae) monitoring. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 30 records from A new river loach from the main channel of the upper Mekong in Yunnan (Cypriniformes: Nemacheilidae). 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 80 records from Pepper French national collection. 211 records from Nezara viridula records held by the Royal Horticultural Society. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 14364 records from JOI - Herbário Joinvillea. 2312 records from Mycological collection of the National Museum. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2477 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 7 records from Revision of fossil Bibionidae (Insecta: Diptera) from French Oligocene deposits. 1650 records from University of Calgary Herbarium. 1 records from A new macropterous species of a rarely collected subfamily (Heteroptera, Tingidae, Vianaidinae). 2029 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 3509 records from Entocytheridae (Ostracoda) World Database. 10 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 31 records from Siphonaptera. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 7574548 records from OEH Atlas of NSW Wildlife. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 25 records from Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex.. 12161 records from ISE - Herbário ISE. 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 457 records from Microbial Observatory of the Laboratoire Arago. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 7 records from Two new marine flatworms (Polycladida: Pseudocerotidae) from Andaman & Nicobar Islands, India. 2 records from Biology and description of Megaprosternum cleonarovorum sp. nov. (Hymenoptera: Bethylidae) a gregarious larval ectoparasitoid of Cleonaria bicolor Thomson (Coleoptera: Cerambycidae) from India. 5098 records from Atlas de los coleóptera Scarabaeoidea de México. Segunda parte. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 712 records from Aprovechamiento sustentable y conservación de la palma bola (Zamia furfuracea), especie endémica protegida, en la zona de Los Tuxtlas, Veracruz. 99300 records from Landesmuseum Kärnten. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 2 records from A new iphiculid crab (Crustacea, Brachyura, Leucosioidea) from the Middle Miocene of Austria, with notes on palaeobiogeography of Iphiculus. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 424 records from The types of Phasmida in the Natural History Museum, London, UK. 787 records from List of Spiders of Prioksko-Terrasnyi Biosphere Reserve. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 3403811 records from A global database for the distributions of crop wild relatives. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 167 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 5 records from Two new species of the genus Phaea Newman, 1840 (Coleoptera: Cerambycidae) from Mexico. 5 records from Two new species in the genus Phoxokalliapseudes Drumm & Heard, 2011 (Crustacea: Tanaidacea: Kalliapseudidae) from the southwestern and southern coasts of Korea. 2 records from Description of the first Oriental species of the ant genus Xymmer (Hymenoptera: Formicidae: Amblyoponinae). 154 records from Tejidos colectados en la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 2 records from Plectranthias takasei, new species of anthiadine fish from southern Japan (Teleostei: Serranidae). 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 14319 records from Dry Tortugas Reef Visual Census 2000. 68 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 16 records from The Steninae MacLeay, 1825 (Coleoptera: Staphylinidae) of Iran: identification key, checklist of species and a new synonymy. 2 records from On the type locality of Sorubim trigonocephalus Miranda-Ribeiro, 1920 (Siluriformes: Pimelodidae). 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 19 records from Copepods (Cyclopoida) associated with top shells (Vestigastropoda: Trochoidea: Tegulidae) from coastal waters in southern Japan, with descriptions of three new species. 1563 records from Mid Ulster Hare Surveys 2012-2015. 2 records from Description of a new species of Lethe (Lepidoptera, Nymphalidae, Satyrinae) from western Yunnan, China. 12289 records from ISM Mammalogy Collection. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 168966 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 8478 records from International Polar Year and Census of Antarctic Marine Life Ross Sea voyage (TAN0802) biodiversity data. 4954 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 2 records from Palaearctic Hoplitis bees of the subgenera Formicapis and Tkalcua (Megachilidae, Osmiini): biology, taxonomy and key to species. 2649 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 191 records from Herpetofauna laguna El Tinije. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1238 records from Insect Collection (CeStuBio). 1 records from Celaeno plicata. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 24132 records from Computarización de abejas de la colección entomológica de la Frontera Sur. 320 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 78 records from The Mysidae (Crustacea: Peracarida: Mysida) in fresh and oligohaline waters of the Mediterranean. Taxonomy, biogeography, and bioinvasion. 23831 records from HUEM - Herbário da Universidade Estadual de Maringá. 4296 records from Diversidad de hemíptera: heteróptera de Baja California e islas del Golfo de California. 38858 records from Ims fish tag database. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 5525 records from Bryophyte diversity in grassland. 67 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 7735 records from CSUC Vertebrate Collection. 8 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 70494 records from HUFU - Herbarium Uberlandense. 1 records from Hoplophora globosa. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 20 records from Heteroptera - SMNG. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 454 records from Copépodos pelágicos del Pacífico norte mexicano. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 33 records from Revision von Suctobelba trigona (Michael, 1888). 2497 records from InsectScale2008FlowerCover. 1030627 records from Phanerogamic Botanical Collections (S). 13912 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 20 records from Truchas Mexicanas. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 20043 records from Mollusca collection of National Museum of Nature and Science. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 3 records from MSB Mammal Observations (Arctos). 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 90189 records from African Rodentia. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 119692 records from Jordal. 271740 records from MVZ Herp Collection (Arctos). 6 records from Three New Species From The Spider Families Amaurobiidae, Thomisidae And Salticidae (Araneae: Arachnida) From India. 22 records from DGGE profiles of selected Gammaproteobacteria from leaf samples. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 2 records from Two new species of the genus Deontolaimus de Man, 1880 (Nematoda: Leptolaimidae) from mangrove ecosystems of Vietnam. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1500 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 1 records from Damaeus concolor. 361 records from Taxonomic revision of the Malagasy Camponotus grandidieri and niveosetosus species groups (Hymenoptera, Formicidae) using qualitative and quantitative morphology. 488 records from The ecology of Najas flexilis (Slender naiad). 7 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 50 records from Fiocruz/CFP - Coleção de Fungos Patogênicos. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 5709 records from Coleoptera of Piska Forest. 2 records from Mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) with oral rim ducts; description of a new genus and species from Turkey, and discussion of their higher classification within the Pseudococcidae. 712 records from Herbier G. Garapin (BOUM). 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 17 records from Systematics of some calloporid and lacernid Cheilostomata (Bryozoa) from coastal South Korean waters, with the description of new taxa. 42 records from Kalyptorhynchia (Platyhelminthes: Rhabdocoela) from KwaZulu-Natal (South Africa), with the description of six new species. 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 1 records from Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian. 5 records from Description of a new kinorhynch species, Paracentrophyes sanchezae n. sp. (Kinorhyncha: Allomalorhagida) from the Gulf of Mexico, with differential notes on one additional, yet undescribed species of the genus. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 6 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 3 records from Irene litanga, a new genus and new species in the Polia generic-complex from China (Lepidoptera, Noctuidae, Hadeninae, Hadenini). 115324 records from University of Vienna, Institute for Botany - Herbarium WU. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 18636 records from Ants from the Paraguayan dry Chaco. 379 records from WNMU Fish Collection (Arctos). 6199 records from SANBI: DNA Banking(1987-2011). 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 9889 records from UConn Mammals. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 44 records from Colección e identificación de las especies de Meloidogyne y su distribución en los cultivos más importantes para México. 3811 records from Captura de datos de la Colección de Curculionoidea (Insecta: Coleoptera) de la Universidad Autónoma de Querétaro. 1998 records from Aves de la cuenca media del río Bogotá. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 5147 records from Códigos de barras de la vida en peces y zooplancton de México. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 6 records from Two new species of the rare genus Nygolaimoides Meyl in Andrássy, 1960 (Nematoda, Dorylaimida, Thorniidae) from Iran, with a compendium of its species. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 1 records from Nothrus runcinatus. 16944 records from UFG - Herbário da Universidade Federal de Goiás. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 5 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 1702 records from BioGIS - Bryophytes - HUJ collections. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 6225 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 327 records from Colección nacional de palmas de Colombia - JBQ. 50 records from Lindesnes. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 77 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 1599 records from Florida Keys Reef Visual Census 2000. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 6 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 16 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 2 records from A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini). 182 records from Revision and cladistic analysis of the Southeast Asian leaf-dwelling spider genus Calapnita Simon (Araneae, Pholcidae). 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 1515 records from Monitoreo del bentos, nutrientes e isótopos en relación a la salud arrecifal de áreas naturales protegidas del norte de Quintana Roo con mayor vulnerabilidad al cambio de fase arrecifal: Primera Etapa. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 159 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 11 records from A Cryptic Invasion in the Western Atlantic: Presence of the Fouling Barnacle Megabalanus zebra (Darwin, 1854) (Crustacea, Cirripedia) in the Caribbean Sea. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 16346 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 11 records from - BID-AF2015-0004-NAC- Collection du Laboratoire d'Entomologie Appliquée de l'université de Lomé. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 2546 records from The atlas of butterflies in Kraków. 233224 records from MVZ Mammal Collection (Arctos). 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 1333 records from Inventario computarizado de la colección de parásitos de peces del noroeste de México. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 70222 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 10075 records from Nematoda of Costa Rica (INBio). 207801 records from Australian National Wildlife Collection provider for OZCAM. 1 records from Zetes longiusculus. 957 records from Computarización de la Colección nacional del phylum Porifera Gerardo Green. 3204 records from Faunal Inventory of Morysin Nature Reserve. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 32 records from Sea Ice Nematodes. 12499 records from WhiteSeaPlankton. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 668 records from Freshwater Macrophyte Survey Data. 89874 records from ecoscope_observation_database. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 360 records from Bee species data, InsectScale 2008. 288 records from Fungi of Słowiński National Park, Poland. 24 records from Transferred depository for twenty-seven holotypes of the plant bug and flower bug species recently described from Thailand (Hemiptera: Heteroptera: Miridae and Anthocoridae). 30414 records from BLS Lichen Database: Welsh churchyards. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 412 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 15 records from A key to the East Palaearctic and Oriental species of the genus Rhysipolis Foerster, and the first host records of Rhysipolis longicaudatus Belokobylskij (Hymenoptera: Braconidae: Rhysipolinae). 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 353 records from Coastal and marine species. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 10358 records from Census of the flora of Benin. 32952 records from Coleção de Aves do Museu Nacional / UFRJ. 1 records from Oppia glaucina. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 180 records from A taxonomic monograph of the leaf-litter inhabiting weevil genus Plumolepilius new genus (Coleoptera: Curculionidae: Molytinae: Conotrachelini) from Mexico, Guatemala, and El Salvador. 25713 records from Museu Paraense Emílio Goeldi - Diptera Collection. 3963 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 184364 records from LACM Entomology Collection. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 38659 records from Biota occurrence data from plankton surveys around New Zealand. 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 23311 records from Bryophyte herbarium, Tromsø Museum. 356 records from Morphologische Daten von Puffinus creatopus. 14396 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleoinvertebrates National Collection (MACNPi). 175 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 80 records from Ecología evolutiva de dos especies invasoras de humedales en la República Mexicana: Arundo donax y Phragmites australis (Poaceae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 158 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 34 records from New records in vascular plants alien to Kyrgyzstan. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 1377 records from Fitoplancton marino frente a Baja California. 1. Bahía de Todos Santos, BC. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 58 records from Museu Paraense Emílio Goeldi - Nematoda Collection. 13597 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 2 records from Two new species of Otiorhynchus Germar, 1822 (Tecutinus Reitter, 1912) from south-western Anatolia (Coleoptera, Curculionidae: Entiminae). 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 57019 records from Online Atlas of vascular plants 2012-2020. 12370 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 198 records from Checklist of the micro- and anophthalmic soil-dwelling weevils of the world (Coleoptera: Curculionidae). 15637 records from CCBER Herpetology Collection. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 53391 records from IAC - Herbário do Instituto Agronômico de Campinas. 5 records from A new species and a new synonymy of the plant bug genus Fulvius from Japan (Hemiptera: Heteroptera: Miridae: Cylapinae). 10007 records from SANT-Lich. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 6 records from Discovery in Japan of the second species of the genus Dolichocentrus Martynov (Trichoptera: Brachycentridae). 60672 records from QLD DERM Coastal Bird Atlas (Trial). 49 records from Nine new species of the genus Deinopteroloma Jansson, 1946 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China and Vietnam. 230 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 2665 records from Pink-permanent surveillance of coastal areas: Odonata. 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 3 records from A new two-pored species of Amphisbaena (Squamata, Amphisbaenidae) from the Brazilian Cerrado, with a key to the two-pored species of Amphisbaena. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 7427 records from Weevils of the Tatra Mts.. 231 records from Variabilidad genética en las poblaciones naturales de la almeja catarina Argopecten ventricosus-circularis (Sowerby II, 1842). 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 561820 records from Bee Biology and Systematics Laboratory. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 1 records from Oribates calcaratus. 8 records from Order Diptera, family Mydidae. 509 records from Flora leñosa de la reserva La Selva El Ocote. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 38816 records from Bryophyte diversity in forests. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 4 records from A new Indian species of Pardoteleia Kozlov & Lê (Hymenoptera: Scelionidae: Scelioninae) and first description of the male. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 8 records from Review of the Ulopella leafhopper genus group (Auchenorrhyncha, Cicadellidae, Ulopinae) with description of a new genus and species collected from pitfall traps in Zambia. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 4 records from Fossil (SMNH-FO). 531 records from Base de datos de las cicadas mexicanas. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 56 records from Guide to the Parasites of Fishes of Canada Part V: Nematoda. 6801 records from UPRM Invertebrate Collection. 2000 records from Herpetofauna de las sierras La Candela, Jerez de García Salinas y El Mastrante. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 2007 records from Palaeobiology collection, FAU Erlangen. 2 records from Two New Jumping Spiders of the Genus Chalcoscirtus from China (Araneae: Salticidae). 10973 records from Evaluación de la situación actual de las poblaciones del pez cachorrito del desierto (Cyprinodon macularius macularius) en la Cuenca del Bajo Río Colorado, Sonora-Baja California, México. 5082 records from Heuschrecken_Raw1. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 1 records from Miriapodi di alcune grotte della Campania. 92 records from Protozoa Abundance_Microbial Parameters. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 6639 records from Laptev Sea and Nansen Basin Zooplankton, 1993. 9 records from Four new species of Lorryia (Acari: Tydeidae) associated with Hevea brasiliensis Muell. Arg. (Euphorbiaceae) in Brazil. 7 records from A new species, first report of a male and new distributional records for three species of Pteroptrix (Hymenoptera: Aphelinidae) from China. 57220 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 13833 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 3 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 4487 records from Portuguese Seaweeds. 120 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 21948 records from HBRG Fungus, Lichen & Lower Plants Dataset. 1284 records from Collection of Heteroptera. 1 records from Cepolacanthus kimi, a new genus and species of copepod (Cyclopoida: Taeniacanthidae) parasitic on Bandfish Acanthocepola abbreviata (Valenciennes, 1835) (Actinopterygii: Cepolidae) caught off the Iraqi coast. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 3 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 11803 records from Computarización de la Colección Nacional de Crustáceos del Instituto de Biología, UNAM y elaboración de su catálogo. 100 records from Review of the genus Siemssenius Weise, 1922 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 26 records from Pachyprotasis kojimai sp. nov. — the “ Pachyprotasis nigronotata ” of Japanese authors (Hymenoptera: Tenthredinidae). 15 records from The identity of Equatobursa, with proposal of new genus and species level synonymies (Hemiptera: Heteroptera: Heterogastridae). 6519 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México: 3a fase. 176 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 151 records from Hidden diversity in deep-water bandfishes: review of Owstonia with descriptions of twenty-one new species (Teleostei: Cepolidae: Owstoniinae). 3 records from Study of the Oriental genus Alishania Vilbaste (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of one new species. 2533 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 10910 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 7 records from New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1047 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 86 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 35325 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 121251 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 8594 records from ColRest_Raw1. 24 records from New species of Thelepodidae (Terebelliformia, Polychaeta) from Taiwan. 3 records from Systematics of a small Gehyra (Squamata: Gekkonidae) from the Einasleigh Uplands, Queensland: description of a new range restricted species. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 4 records from Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 4579 records from Herbarium WRSL, Flora of the Silesia. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 304 records from Bryophytes of Glen Nevis Woods 1987-1988. 3336 records from Bryophytes, fungi and lichens on dead wood. 829 records from Colección Hidrobiológica del Chocó. 581337 records from AntWeb. 84072 records from Actualización de la Colección de Artrópodos con importancia médica (CAIM), Laboratorio de Entomología, InDRE. 17 records from A new species and new records of the genus Neotarsonemoides Kaliszewski, 1984 (Acari: Tarsonemidae) from East Azerbaijan province, Northwestern Iran. 67 records from Australian mycophagous species of the genus Deplorothrips (Thysanoptera, Phlaeothripinae). 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 36 records from Retrocitomyia Lopes, 1982 (Diptera: Sarcophagidae): new species, new records, key to males, and an updated catalog. 3462 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 73 records from AMF colonization in Plantago. 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 11 records from The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5733 records from Small Mammal Research Database. 3 records from A millipede missing link: Dobrodesmidae, a remarkable new polydesmidan millipede family from Brazil with supernumerary rings (Diplopoda, Polydesmida), and the establishment of a new suborder Dobrodesmidea. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 5 records from New genus and species of ant-like true bug (Hemiptera: Miridae) from the Canary Islands. 16 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 73729 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 1 records from Ankerius aenigmaticus, a new genus and new species of aphanodactylid crab symbiotic with polychaetes from the Red Sea coast of Saudi Arabia (Crustacea: Decapoda: Brachyura: Aphanodactylidae). 704 records from Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 5 records from Two new species of Stigmaeidae (Acari: Trombidiformes: Rhaphignathoidea) from Brazil. 812 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 231 records from Shannon Index and species richness for arthropods. 4050 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 177466 records from CAS Entomology (ENT). 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 1 records from Red list project inventory, bryophytes. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 2 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 2116 records from Collection entomologique Pierre Lachiver. 3 records from Dinosaurs from the Cretaceous of South China. 1080 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 4993 records from Otter in coastal areas - Carcasses. 64 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 485 records from National Taiwan Ocean University. 6 records from Two new species of Melanorivulus (Cyprinodontiformes: Cynolebiidae) from Rio Verde drainage, Upper Rio Paraná basin, Brazil. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 3 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 259949 records from Zoology (Museum of Evolution - Uppsala). 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 1 records from Lissotes working-group. 4847458 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2 records from Range extension of the rare braconine genus, Lyricibracon Quicke (Hymenoptera: Braconidae), with the description of a new species from India. 1 records from Oribates fuscipes. 9 records from A new species of Monstrilla Dana, 1849 (Copepoda: Monstrilloida: Monstrillidae) from Korea, including a key to species from the north-west Pacific. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 690 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 1196 records from Entomological collection of the National Museum. 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 1 records from Zetes cespitum. 13253 records from CHAS Ornithology. 920284 records from PlutoF platform observations. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 26397 records from Herbarium Senckenbergianum (GLM) - Lichenes. 22804 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 36 records from First Inventory of Sea Anemones (Cnidaria: Actiniaria) of the Mexican Caribbean. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 233 records from Taxonomy of the genus Chlamisus Rafinesque (Coleoptera: Chrysomelidae) from China with description of three new species. 48803 records from SPSF - Herbário Dom Bento José Pickel. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 76 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2562 records from Inventario de la vegetación acuática vascular de cuatro regiones hidrológicas prioritarias del centro de México. 1704 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 9077 records from Actualización y adiciones a la Colección de Poliquetos del Instituto de Ciencias del Mar y Limnología, UNAM. 6 records from Coleção de Tardigrada do Museu Nacional - UFRJ. 2 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 1 records from Nothrus segnis. 1 records from Hoplophora ferruginea. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 63415 records from MMNS Ichthyology Collection. 499 records from Seasonal dynamics of sub-ice fauna below pack ice in the Arctic (Fram Strait). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 30952 records from SANT-Algae. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6237 records from Plecoptera. 18772 records from RHS lily beetle (Lilioceris lilii) monitoring. 151183 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 8 records from Cave species of the genus Anurida (Collembola: Neanuridae) from Korea, with the description of new species. 361 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 9 records from On the generic placement and taxonomic status of some Miltochrista taxa described by Franz Daniel (Lepidoptera, Erebidae, Arctiinae). 10 records from Description of a new species of the Afrotropical spider genus Afroneutria (Araneae, Ctenidae). 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 3057 records from Florida Keys Reef Visual Census 2010. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 23658 records from ZUEC-AMP - Coleção de Anfíbios do Museu de Zoologia da UNICAMP. 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 130 records from Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review. 1124142 records from PRECIS. 29 records from Genetic variation of the 30 beech stands across three exploratories. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 4464 records from Passalidae y Lucanidae (Coleoptera: Scarabaeoidae) de México. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 1219 records from Dutch Butterfly Monitoring Indexes. 8 records from Colección de Referencia de Urocordados del Museo de Ciencias de la Universidad El Bosque. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 41094 records from CSIRO Ichthyology provider for OZCAM. 54415 records from Cawthron Institute freshwater invertebrate data. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 369837 records from Herbario Nacional Colombiano (COL). 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1 records from Celaeno obsoleta. 58 records from New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini). 1 records from Spongillaflies (Neuroptera, Sisyridae) in Baltic amber. 434 records from Distribución, abundancia y hábitat de la liebre endémica Lepus flavigularis. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 283 records from HSU Vertebrate Museum Birds Collection. 341 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1201 records from Monocotyledonous Geophytes of Fergana Valley. 1678 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 758592 records from Fishbase. 6 records from A new genus of freshwater crab of the tribe Kingsleyini Bott, 1970 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) with description of a new species from Mato Grosso, Brazil. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 5194 records from SMNS Palaeontological collection - Amber and fossil insects. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 3539 records from Naturalis Biodiversity Center (NL) - Pisces. 29 records from Opistognathus ensiferus, a new species of jawfish (Opistognathidae) from the Gulf of Mannar, India, with redescription of O. solorensis Bleeker. 5 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Oribates gilvipes. 389 records from Amphibian and Reptilian (KIEE-AR). 9 records from Australian freshwater sponges with a new species of Pectispongilla (Porifera: Demospongiae: Spongillida). 94696 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 10000 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 1123 records from Inventario de especies de vertebrados para apoyar la creación del Ordenamiento Ecológico y la Reserva de la Biósfera Janos, Chihuahua. 1910 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 83 records from Fiocruz/COLPROT - Coleção de Protozoários. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 6541 records from Likona Invertebrates. 3 records from An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea). 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 14590 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 7 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 5817 records from Flora del municipio de Culiacán, Sinaloa. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 28838 records from EPA River Biologists data. 190 records from Relative abundance of ostracods in sediment core Sv09. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 5506 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 198 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 2270 records from UTEP Plants (Arctos). 135 records from Registros biológicos recogidos en el marco del proyecto Census of Marine Life Componente Natural Geography in Shore Areas - NAGISA Santa Marta. 130222 records from Occurrence records of southern African aquatic biodiversity. 8 records from Helfer H. 1936. The fishery grounds near Alexandria. VIII Pantopoda. Notes et memoires No 16. 7693 records from NHM, Heteroptera. 4766 records from Paläontologie Marburg. 1 records from A new species of the genus Rhinoecetes Just, 1983 (Crustacea: Amphipoda: Ischyroceridae) from Japan. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 7275 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 6790 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 3 records from First record of the thread-legged assassin bug genus Proguithera from Japan, with description of a new species (Hemiptera: Heteroptera: Reduviidae). 1930 records from Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 555 records from Review of Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae) from Espíri- to Santo, Brazil, with description of twenty-one new species. 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 25 records from Hyolithen - SMF. 16 records from Taxonomic review of the genus Wasmannia.. 17618 records from BioGIS - Mammals - INPA database. 145959 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 2 records from A new species of Prohatschekia Nunes-Ruivo, 1954 (Siphonostomatoida: Hatschekiidae) from the scorpaenid fish, Scorpaena neglecta Temminck & Schlegel, 1843 (Scorpaeniformes: Scorpaenidae), in Korean waters. 926 records from Sistemática molecular y poblacional de especies del género Chirostoma (Pisces: Atherinidae). 5 records from The natural history and morphology of two bromeliad associated hispines from Brazil: Acentroptera basilica Thomson, 1856 and A. cf. tessellata Baly, 1958 (Coleoptera: Chrysomelidae: Cassidinae: Sceloenoplini). 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 25 records from Metrocoris Mayr (Insecta: Hemiptera: Gerridae) of India with descriptions of five new species. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 29 records from Observations on the Biology of Afrotropical Hesperiidae (Lepidoptera) with particular reference to Kenya. Part 11. Heteropterinae. 12 records from New species of Rhorus Förster, 1869 (Hymenoptera: Ichneumonidae: Ctenopelmatinae) from South Korea. 71712 records from SPF - Herbário da Universidade de São Paulo. 28 records from Phthinia Winnertz (Diptera: Mycetophilidae): new species and records from the Neotropical and Oriental regions. 32 records from On the mammals collected by Friedrich Sellow in Brazil and Uruguay (1814 – 1831), with special reference to the types and their provenance. 17 records from The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history. 8 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 40 records from Cerambycidae (Insecta: Coleoptera) of Quixadá, Ceará State, Brazil: new records and new species. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 70788 records from SANT Herbarium vascular plants collection. 7 records from Collection Myriapoda - SNSD. 782 records from Genética poblacional y filogeografía de las tortugas marinas golfina (Lepidochelys olivacea) y laúd (Dermochelys coriacea) en el Pacífico mexicano. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 5103 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 6 records from Description of two new species from China in a new species group of the fig wasp genus Sycophaga Westwood (Hymenoptera: Chalcidoidea: Agaonidae: Sycophaginae). 1 records from A Late Cretaceous diversification of Asian oviraptorid dinosaurs: evidence from a new species. 2513 records from Carabidae of the Tatra Mts.. 2 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 9349 records from Harriet Irving Botanical Gardens (HIBG). 1 records from Miriapodi di alcune grotte della Campania. 9801 records from Programa Integral de Protección de tortugas marinas. Temporadas 2007 a 2012. 20 records from A mountain of millipedes IV: Species of Prionopetalum Attems, 1909, from the Udzungwa Mountains, Tanzania. With notes on “ P. ” fasciatum (Attems, 1896) and a revised species key (Diplopoda, Spirostreptida, Odontopygidae). 89919 records from New Zealand Freshwater Fish Database. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 763 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 5 records from First records of Pseudodoros nigricollis Becker (Diptera: Syrphidae) from Cyprus. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 16 records from Endemism and long distance dispersal in the waterfleas of Easter Island. 384 records from New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda). 167515 records from KUBI Mammalogy Collection. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 601868 records from SEFSC CAGES Alabama Fish Length Data with CPUE. 16 records from Projeto Abrace o Boto Cinza. 4447 records from Lepidoptera (Observations). 495 records from Taxonomic revision of Stigmatomma Roger (Hymenoptera: Formicidae) in the Malagasy region. 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 10577 records from Biological Reference Collections ICM CSIC. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 8771 records from Las familias Polyporaceae sensu stricto y Albatrellaceae en México. 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 624 records from Collection of botanical drawings by Georg Schweinfurth at B. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 372 records from Colección de Entomología - Arthropoda. 1381 records from Fiocruz/CCFF - Coleção de Culturas de Fungos Filamentosos. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 24 records from Review of the genus Defilippia Lioy (Bombyliidae, Diptera) from Egypt, with description of a new species, new combinations, and a neotype designation for D. pharaonis (Paramonov, 1928). 268 records from MCME UPLB Museum Plant Collection. 50670 records from UFP - Herbário UFP - Geraldo Mariz. 31 records from New and poorly known Palaearctic fungus gnats (Diptera, Sciaroidea). 702 records from HSU Vertebrate Museum Reptile Collection. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 57 records from T-RFLP Acidobacteria 2008 RNA ProFIL. 444 records from Insect Collection from New Caledonia. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 28 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 1125 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 19 records from New tribe Labiobaetini tribus n., redefinition of Pseudopannota Waltz & McCafferty 1987 and descriptions of new and little known species from Zambia and Uganda. 8 records from Amended diagnosis of the genus Nannodiaptomus (Copepoda, Calanoida), based on redescription of N. phongnhaensis and description of a new species from caves in central Vietnam. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3182 records from Finnish Entomological Database: Heteroptera. 544 records from Naturalis Biodiversity Center (NL) - Foraminifera. 7509 records from Perot Museum of Nature and Science. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 61 records from Registros restauración ecológica- Magdalena medio. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 10838 records from Evaluación del estado de conservación de las poblaciones de Passerina ciris, P. leclancherii, P. amoena, P. rositae, P. caerulea, Cardinalis cardinalis y C. sinuatus en México: recomendaciones para su conservación y aprovechamiento sustentable. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 41984 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 1 records from Simulium (Gomphostilbia) lemborense, a new black fly species (Diptera: Simuliidae) from Flores, Indonesia. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 77 records from Empria and Monsoma in Japan. 99463 records from NPL collections. 5 records from On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae). 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 19206 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 612934 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 18 records from Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy. 99 records from French national collection of Solanum tuberosum. 27 records from Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 226 records from Tejidos colectados en la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 52 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 107293 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 2011 records from Local BioBlitz Challenge 2013. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 3 records from Ituglanis compactus, a new species of catfish (Siluriformes: Trichomycteridae) from the rio Jari drainage, lower Amazon, Brazil. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 73975 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 1262 records from Taxonomía de los pinos del noreste de México. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 2 records from A new skate genus Orbiraja (Rajiformes: Rajidae) from the Indo-West Pacific. 9688 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 11 records from Allopatric color forms of Scaphidium morimotoi Löbl, 1982 (Coleoptera, Staphylinidae, Scaphidiinae) endemic to the Amami Islands, the Ryukyus, Japan. 2 records from Epidaus wangi (Hemiptera: Heteroptera: Reduviidae), a new assassin bug from Tibet, China. 1092555 records from FLORIVON. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 44744 records from Dry Tortugas Reef Visual Census 2014. 132439 records from HBRG Insects Dataset. 3282 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 53109 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 1964 records from VMNH Invertebrate Paleontology. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 47499 records from Sphaeroceridae Collection. 2307 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 18055 records from Cercle des mycologues de Montréal Fungarium (CMMF). 3578 records from MBML-Mamiferos - Coleção de Mamíferos. 198900 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 409 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 21 records from On the genus Elasmopus Costa, 1853 from the Northeastern Coast of Brazil with five new species and new records. 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 3102 records from Macroalgas marinas de la Región de Zihuatanejo, Gro.. 5 records from A new species of Cicadatra Kolenati, 1857 from China, with primary phylogenetic analyses of the tribe Cicadatrini (Hemiptera: Cicadidae). 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 258 records from Conocimiento y conservación de las mamilarias endémicas del Valle de Tehuacán-Cuicatlán. 2247404 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1329 records from API_CRSN_Data. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 7671 records from HERBAM - Herbário da Amazônia Meridional. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 26835 records from Herbario Pontificia Universidad Javeriana. 16 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 2174 records from MLZ Mammal Collection (Arctos). 124472 records from ICN - Herbário do Instituto de Ciências Naturais. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 14 records from A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae). 9 records from Contributions to the knowledge of the biodiversity of Heteroptera (Insecta) in the Southern Cone, Argentina. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 5267 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 8 records from Notes on the genus Larnaca Walker, 1869 (Orthoptera: Gryllacridinae) from China. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 2467 records from Proyecto interno ejecutado por la CONABIO: Los manglares de México: estado actual y establecimiento de un programa de monitoreo a largo plazo: 2a y 3era etapas. 1 records from The first described male Tube-web Spider for mainland Australia: Ariadna kiwirrkurra sp. nov. (Araneae: Segestriidae). 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 18 records from The genus Microptila Ris (Trichoptera, Hydroptilidae) in Japan. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 68838 records from IICT Herbário LISC. 51110 records from Karplanter i vernet barskog og edelløvskog. 80000 records from Herbario Universidad de Antioquia (HUA). 5 records from A new genus and new species of Cicadettini (Hemiptera: Cicadidae: Cicadettinae) from Pakistan. 2 records from Note sur les fourmis du Musée Zoologique de l'Académie Impériale des Sciences à St. Pétersbourg.. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 168 records from Estudio poblacional y conservación del mono araña (Ateles geoffroyi yucatanensis) en la región nororiental Península de Yucatán. 161336 records from Lund Museum of Zoology - Insect collections (MZLU). 99 records from Observations on the biology of Afrotropical Hesperiidae (Lepidoptera) with particular reference to Kenya. Part 10. Pyrginae, Carcharodini. 1 records from A new species of the genus Tetratoma Fabricius (Coleoptera, Tetratomidae) from China. 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 1995 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 44 records from Diversity of Scydmaeninae (Coleoptera: Staphylinidae) in Upper Eocene Rovno amber. 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 3 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 89699 records from URM - Herbário Pe. Camille Torrand. 634257 records from Inventario Español de Especies Terrestres (MAGRAMA). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 3 records from A new species of the genus Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae) from China. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 228 records from An annotated checklist of the Chilopoda and Diplopoda (Myriapoda) of the Abrau Peninsula, northwestern Caucasus, Russia. 1 records from On centipedes (Chilopoda) of Albania, 2. 84083 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from Nothrus biciliatus. 3 records from Note su alcune specie di chilopodi della regione palestinese. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 346643 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 39872 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 652 records from Spider species diversity from wet and dry habitats. 1374 records from A nest-site survey of Barn swallow at railroad stations in the Kinki District,south-central Japan. 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 1 records from Hoplophora decumana. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 596 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 17024 records from Árboles de Chiapas: registro georreferenciado de los ejemplares depositados en el herbario de la Academia de Ciencias de California (CAS). 597 records from Collection Crustacea - KAUMM. 2113 records from Flora ficológica de la huasteca potosina. 265 records from 16S rRNA gene (V2-V3 region) based analysis of soil procaryotic community composition, Alb VIPs 2008. 88 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 8 records from Five new feather mites of the subfamily Pterodectinae (Acariformes: Astigmata: Proctophyllodidae) from passerines and hummingbirds (Aves) of Brazil. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 13 records from Two new species of Neocorynura from Guatemala (Hymenoptera: Halictidae: Augochlorini) with a key to the species known from the country. 44 records from Solanum_baretiae. 3643 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 1521 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 10689 records from Inventario de la fauna arrecifal asociada al ecosistema de Pocillopora en el Pacífico Tropical Mexicano. 15 records from On the Ampedini Gistel, 1848 (Coleoptera: Elateridae) of Central Asia, with a description of a new species of the genus Reitterelater Platia & Cate, 1990. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 38 records from Revision of the Rhinophoridae (Diptera: Calyptratae) of Japan. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 9 records from Eusyllinae, Exogoninae and Autolytinae (Syllidae: Polychaeta) from the Southern Mexican Pacific, with the description of three new species. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 2 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 1 records from Oribates flammula. 4 records from A new species of the genus Anthalona Van Damme, Sinev & Dumont, 2011 (Cladocera: Anomopoda: Chydoridae) from North-East Thailand. 51 records from Estudio poblacional y parámetros hematológicos de la zorra norteña Vulpes macrotis zinseri Benson en la Región del Tokio, México. 3257 records from fundiv france database. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 1 records from Eremaeus hepaticus. 6817 records from Colección de Reptiles del Instituto Alexander von Humboldt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 10065 records from Malezas introducidas en México. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 13993 records from Herpetology. 3000 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 110660 records from The avian collection at the Natural History Museum, Oslo, Norway. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 2392 records from Fongs d'Andorra. 1244 records from Abundanz_Infloreszenzenschlupf_Subplotebene_2008. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 1004 records from National Museum of Marine Biology and Aquarium. 27 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 167 records from Código de barras de diferentes grupos de peces mexicanos endémicos de la Mesa Central Mexicana. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 151 records from Protozoa abundance and microbial parameters, 2008 and 2009. 8937 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Cepheus latus. 493270 records from Entomology, Natural History Museum, University of Oslo. 1000 records from Demografía e historia de vida de la lagartija Xenosaurus newmanorum en Xilitla, San Luis Potosí. 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 114 records from qPCR Ribosomecontent Explo 2008. 3895635 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 255 records from Inventario de Plantas Mámbita. 44 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 53120 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 31 records from A new Subleuconycta (Lepidoptera: Noctuidae: Acronictinae) species from Taiwan. 253105 records from Lyman Entomological Museum (LEMQ). 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 1 records from Pelops torulosus. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 325 records from The genus Manota Williston (Diptera: Mycetophilidae) in Peruvian Amazonia, with description of sixteen new species and notes on local species richness. 54 records from Revision of the spider genus Gippsicola Hogg, 1900 (Araneae: Segestriidae). 25053 records from NBMP Roost Count. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 173415 records from Hymenoptera specimen database of Kyushu University. 2 records from Two new species of Bungona Harker, 1957 (Ephemeroptera: Baetidae) from Borneo, Indonesia. 6855 records from Echinoderm collection of National Museum of Nature and Science. 1 records from Oribates picipes. 35901 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 2337 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 13086 records from Collection of Coleoptera. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 52 records from Isotope tracer experiment: meiofauna counts. 5 records from A new species of Australian frog (Myobatrachidae: Uperoleia) from the New South Wales mid-north coast sandplains. 5053399 records from Southern African Bird Atlas Project. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 63 records from (Data S1) Palynology of ODP Site 119-739. 332 records from The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae). 24945 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 2 records from Eocene lantern fruits from Gondwanan Patagonia and the early origins of Solanaceae. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 2576 records from Hosted Invertebrate Collection 01. 1489 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 374 records from published Chenopodium vulvaria observations. 455 records from SIO_FAMIZ. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 7403 records from Fishes in MZNA-VERT: freshwater fishes of Hidalgo state (Mexico). 5701 records from Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 353 records from New species of the damselfly genus Argia from Mexico, Central America and Ecuador with an emphasis on Costa Rica (Insecta: Odonata: Coenagrionidae). 585 records from Ascomycetes of Russian Fennoscandia. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 4854 records from Inventario de las especies de hongos microscópicos en el Valle de Zapotitlán, estado de Puebla. 506 records from Inventory of Dogo-Kétou forest (South-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 25 records from Four new species, taxonomic, and nomenclatural notes in Hammatoderus Gemminger & Harold, 1873 (Coleoptera, Cerambycidae, Lamiinae). 6 records from Two new planthopper species (Hemiptera, Fulgoroidea, Caliscelidae) collected in pitfall traps in Zambia. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 11 records from Pteroceraphron Dessart new to the USA (Hymenoptera: Ceraphronoidea). 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 104 records from Biología reproductiva de Hechtia schottii Baker ex Hemsley (Bromeliaceae), una especie dioica y rara de la Península de Yucatán. 5 records from Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus. 40632 records from IMOS - AusCPR: Phytoplankton Abundance. 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 44 records from Ecología y comportamiento de dos carnívoros del Bolsón de Mapimí, Durango. 506 records from Nemátodos acuáticos de vida libre de Quintana Roo. 21 records from Paroxythrips gen. n. (Thysanoptera, Thripidae), associated with the gymnosperm order Araucariales in Japan and Australia. 3 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 1163 records from Detección de reclutas de la dorada Sparus aurata como medida del nivel de establecimiento en la Bahía de La Paz, BCS. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 5850 records from UAFMC Fish. 119366 records from The digitization of plant specimens of NTU. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 603 records from Oat French National Collection. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 71 records from Colección de Referencia de Peces del Museo de Ciencias de la Universidad El Bosque. 481 records from IPOE_Benthos_Steffens. 839 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 23 records from Taxonomy and ecology of a new species of Corynura (Hymenoptera: Halictidae: Augochlorini) from Chile and Argentina. 1746416 records from SA Flora (BDBSA). 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 3633 records from Census of medicinal and agroforestry plants of Benin. 495704 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 77 records from Xiphosura collection of National Museum of Nature and Science. 80128 records from NCSM Fishes Collection. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 1518 records from Florida Keys Reef Visual Census 1997. 365 records from Colección Herpetológica de la Patagonia. 1359 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 8881 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 55317 records from Local Wildlife Site Surveys Berkshire. 55 records from Galls on Beech Trees in Hainich, 2008. 2 records from A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia. 1481 records from Reptilia notes, NTNU University Museum. 11 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 2082 records from Vietnam Type Culture Collection. 5 records from Review of the genus Sophonia (Hemiptera: Cicadellidae) with three new species from India. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 1680 records from Avifauna del Altiplano de San Luis Potosí. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 57 records from Eight new species of MacvIcarIa Gibson and Bray, 1982 (Digenea: Opecoelidae) mainly from endemic temperate marine fishes of Australia. 27324 records from Radiolaria specimens from the Norwegian Sea. 484 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 84 records from Colección de Referencia de Equinodermos del Museo de Ciencias de la Universidad El Bosque. 1 records from Il popolamento dell'Appennino meridionale: dall'Appennino campano alle serre calabre. Osservazioni sui chilopodi dell'Appennino lucano e calabrese (Chilopoda). 5 records from On Jungicephus Maa (Hymenoptera: Cephidae) with description of a new species from China. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 1051 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 403 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 66498 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 4266 records from UAFMC Birds. 655 records from Data collected on animal species through census using Kilometric Abundance Index (KAI) in Biosphere Reserve of W-Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 5414 records from Ontario BioBlitz Species Records. 72686 records from NINA Vanndata øvrige arter. 1 records from A new Garcorops species from Madagascar copal (Araneae: Selenopidae). 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 3 records from Unraveling a new lineage of Hydrobiidae genera (Caenogastropoda: Truncatelloidea) from the Ponto-Caspian region. 20 records from A review of the genus Eotmethis (Orthoptera, Acridoidea, Pamphagidae) with two new species and key to known species of the genus from China. 77599 records from Avifauna de la Reserva de la Mariposa Monarca. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 138919 records from AM: Freshwater Invertebrates (1900-2005). 5623 records from South African National Diatom Collection (SANDC). 198 records from Tortue Olivâtre. Données publiées dans le cadre du projet JRS Bénin. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 11623 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 2 records from Capitella ambonensis: a new polychaete species (Annelida: Capitellidae) collected from a mangrove habitat on Ambon Island, Indonesia. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 67236 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 1472 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 12512 records from ULg_Hexapoda. 2880 records from Coleoptera, NEF. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 1655 records from Florida Keys Reef Visual Census 1995. 223486 records from Phytochorologie des départements français. 11 records from Pollen profile from sediment core AV14_K2-4. 10864 records from Lichen diversity in forests. 61745 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 2 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 9 records from Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea. 401 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 347 records from Peces, ictioplancton y helmintos parásitos en la Bahía de Chetumal (Santuario del Manatí). 4761 records from SMDB - Santa Maria Departamento de Biologia. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 623 records from Estudio monográfico del género Echinopepon Naud. (Cucurbitaceae) en México. 12 records from New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 471 records from Aschelminth collection of National Museum of Nature and Science. 5 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 387192 records from BioFokus. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 90 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 27964 records from Amphibian Specimens. 1 records from Cryptic within cryptic: genetics, morphometrics, and bioacoustics delimitate a new species of Eleutherodactylus (Anura: Eleutherodactylidae) from Eastern Cuba. 226815 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4498 records from Colección Herbario Universidad Católica de Oriente. 355 records from Culture Collection of Cryophilic Algae. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 7187 records from Estudio florístico, ecológico y etnobotánico, en el área natural protegida "Tenancingo-Malinalco-Zumpahuacan", Estado de México. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 767 records from BioGIS - Bats - Asaf Tsoar database. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 24 records from Ice Diatoms Arctic Basin 1977, 1980. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 4 records from Description of the first species of Gonadryinus Olmi (Hymenoptera, Dryinidae) from the Afrotropical region. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 7366 records from Caracterización y monitoreo de la condición arrecifal en cinco áreas naturales protegidas y un área de influencia de Quintana Roo, México: Primera etapa. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 4977 records from Florida Keys Reef Visual Census 2007. 5 records from Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta. 810 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 161 records from Orthoptera (Insecta: Tettigonioidea, Pyrgomorphoidea, Acridoidea) of Kafa Biosphere Reserve, Bale Mountains National Park and other areas of conservation interest in Ethiopia. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 324 records from Estimación de biomasa de abulón Haliotis spp. en la zona de Bahía Tortugas, BCS. 10034 records from UAM Fish Collection (Arctos). 62 records from Archaea Collection in BCRC. 27 records from First occurrence of Nemobiinae crickets in the Lesser Antilles (Orthoptera, Grylloidea, Trigonidiidae), with the descriptions of three new species. 47357 records from DMNS Bird Collection (Arctos). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 81329 records from natagora-earlybirds. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 2 records from Arthropoden aus südostalpinen Höhlen.. 2 records from n the type species of the genus Aetius O. Pickard-Cambridge, 1896: The first description of male with notes on cymbial notch and mating plug (Araneae: Corinnidae: Castianeirinae). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3688 records from Clare Biological Records Centre dataset. 9 records from A new species of Acanthocaudus Smith (Braconidae: Aphidiinae), with a key to species and new host and distribution records for aphidiines associated with Silphium perfoliatum L. (Asterales: Asteraceae). 12434 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 3945 records from TTRS Ornithology. 15640 records from The Fish Collection at the Zoologische Staatssammlung München. 2344 records from Species composition of protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of JRS Biodiversity Foundation project. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1 records from Zetes rubens. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 384654 records from University of Florida Vertebrate Paleontology. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 582 records from Bioblitz 2013 Copenhagen Denmark. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 301059 records from Coordinated Waterbird Counts. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 1 records from Nothrus pollinosus. 2 records from A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey. 9879 records from Bibliographic records of Angola mammals. 13 records from Revalidation of Platystigma Kennedy, 1920, with a synopsis of the quadratum species group and the description of three new species (Odonata: Pseudostigmatidae). 12051 records from ISM Ornithology Collection. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 2 records from Spelaeogammarus uai (Bogidielloidea: Artesiidae): a new troglobitic amphipod from Brazil. 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 7 records from Description of Eutetrapha weni n. sp. from Guizhou, China (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 36356 records from Dry Tortugas Reef Visual Census 2012. 12 records from The genus Dromanthomorphus Pic, 1921 (Coleoptera, Cleroidea: Malachiidae) in South-East Asia. 23115 records from Naturalis Biodiversity Center (NL) - Odonata. 1004 records from Colección de microorganismos del CINVESTAV-IPN Fase I, Base de datos, Parte Vista Usuarios Internos. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 15 records from A new species of Cynopotamus Valenciennes, 1849 (Characiformes, Characidae) with a key to the species of the genus.. 46 records from Coleção de Nematomorpha do Museu Nacional - UFRJ. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 76435 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 2686 records from Análisis de viabilidad para poblaciones de la cactácea amenazada Ariocarpus trigonus. 255 records from GENT Lactarius Deliciosi. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 1423 records from Algas coralinas articuladas (Rhodophyta-corallinales) de México. 207 records from BioAcoustica: Wildlife Sounds Database. 1 records from Myriopoden von Epirus. 8 records from A new species of Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) from Amazon basin, Brazil. 19 records from A new species of Protaetia Burmeister, 1842 from Armenia with taxonomic notes on Cetonia floricola fausti Kraatz, 1891 (Coleoptera: Scarabaeidae: Cetoniinae). 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 4 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 789 records from SDSM Vertebrate Paleontology Collection. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 102 records from Sipuncula collection of National Museum of Nature and Science. 588 records from Relative abundance of ostracods in sediment core Lz1120. 2 records from Four new nematode species (Araeolaimida: Comesomatidae, Diplopeltidae) from the New Zealand continental slope. 46 records from Three new Sisyphus species (Coleoptera: Scarabaeidae: Scarabaeinae) from shaded vegetation in southern Africa. 6584 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 11 records from Germalus species of the Malagasy region (Heteroptera: Lygaeoidea: Geocoridae). 1832 records from National Earthworm Recording Scheme Records (Great Britain). 26624 records from Monitoring data from the federal state Bavaria (Germany). 155140 records from Museu Paraense Emilio Goeldi Herbarium. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 4 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 59 records from Further studies on south eastern Asian Luciolinae: 1. Sclerotia Ballantyne, a new genus of fireflies with back swimming larvae 2. Triangulara Pimpasalee, a new genus from Thailand (Coleoptera: Lampyridae). 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 12 records from The taxonomic status and sister group relationship of the cardinalfish species Jaydia striatodes (Percomorphaceae: Apogonidae). 156 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 2654 records from Collection of Hymenoptera. 1 records from On the genus Sunius Curtis, 1829 of Turkey. IV. A new micropterous species from southwestern Anatolia and additional records (Coleoptera: Staphylinidae: Paederinae). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1 records from Miriapodi di alcune grotte della Campania. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 3606 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 397 records from Danish Lacewings (Neuroptera). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 13884 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 1 records from Nothrus pigerrimus. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 102 records from Macroalgas marinas de Baja California Sur Parte I: Bahía de la Paz y Bahía de la Ventana. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 2 records from Saitis lusitanicus Simon, 1901 is a junior synonymn of ' Euophrys' difficilis (Simon, 1868) (Araneae: Salticidae). 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 175 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 953 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 12005 records from Inventario florístico de la familia Boraginaceae en México. Fase II. 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Taxonomic considerations on Lobocneme Rehn, 1911 and Paroxyopsis Rehn, 1911 and a new synonymy (Insecta Mantodea: Stagmatopterinae). 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 29 records from Taxonomic review of the genus Atlantodesmus Hoffman, 2000 (Polydesmida: Chelodesmidae). 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 8739 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 54615 records from CESJ - Herbário Leopoldo Krieger. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 1 records from On the occurrence of caligids (Copepoda: Siphonostomatoida) in the marine plankton: a review and checklist. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 1374 records from MODIRISK:RBINS Diptera: Culicidae Collection. 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 13717 records from OUPR - Herbário "Professor José Badini". 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 45 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2 records from Youngest representative of the extinct genus Microphorites in the Eocene amber of France (Diptera: Dolichopodidae: Microphorinae). 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 22137 records from Global compendium of Aedes albopictus occurrence. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 20 records from A new species of Nemipterus (Perciformes: Nemipteridae) and first record of N. nematophorus (Bleeker) from Taiwan. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 6 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 192948 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 907 records from Base de datos de la familia Fagaceae en el estado de Hidalgo. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 2640 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 155 records from Megophthalmidia_of_North_America. 14416 records from Records from the RHS insect reference collection. 244 records from Revision of Ogdoecosta Spaeth 1909 with description of Ogdoecosta paraflavomaculata López-Pérez, sp. nov. (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini). 111 records from Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 25830 records from Diatomeas (Bacillariophyceae) y Dinoflageladas (Dinophyceae) planctónicas más frecuentes en la región sur del Golfo de México. 13 records from First Amazonian species of Maracaynatum, with comments on the genus (Opiliones: Laniatores: Samoidae). 17062 records from Coastal Saltmarsh Monitoring. 58 records from Mamíferos laguna El Tinije. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3377 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 189408 records from NINA insect database. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 4 records from A new species of Chirothripoides (Thysanoptera: Tubulifera) from India and Malaysia. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 2 records from Two new species of Mexican Rhinotragini and transference of Odontocera josemartii Zayas, 1956 to Stenopseustes (Coleoptera, Cerambycidae). 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 90 records from Apteronotus eschmeyeri, a new species of ghost knifefish from the Magdalena Basin, Colombia (Gymnotiformes: Apteronotidae).. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 14520 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 14518 records from HAS-Algae - Coleção Ficológica do HAS. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 1 records from Zetes ephippiatus. 11 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 35545 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 11 records from A new Aceria species (Acari: Eriophyidae) from Spain on Pycnocomon rutifolium (Dipsacaceae) and supplementary descriptions of Aceria eucricotes and A. kuko from Lycium spp. (Solanaceae). 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 6181 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. 10. Amphipoda Benthonica. Notes and memoirs no 11. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 565 records from Ectomycorrhiza species on all VIP´s April 2008. 2 records from Études myrmécologiques en 1886.. 5441 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 91 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 7410 records from Helgeland Museum, Lepidoptera. 873 records from Kartlegging av spredning av fremmede bartrær. 15879 records from HAMAB - Herbário Amapaense. 1420 records from Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 1 records from Zetes fuscomaculatus. 21647 records from National River Water Quality Network Database (Macro-invertebrates). 208 records from Inventory of Synsepalum dulcificum Daniell in south Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 2 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 22041 records from CUMV Mammal Collection (Arctos). 151 records from Molluscan fauna of Gueishan Island of Taiwan. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 820552 records from Fauna Atlas N.T.. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 52 records from CIM Specimens. 10 records from A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 14 records from New species and new synonyms in European Platypalpus (Diptera: Hybotidae). 31 records from Resolving the status of Pyriporoides and Daisyella (Bryozoa: Cheilostomata), with the systematics of some additional taxa of Calloporoidea having an ooecial heterozooid. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 1952 records from ISM Ichthyology Collection. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 8366 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 60165 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 1 records from Notes on Cataglyphis Foerster, 1850 of the bicolor species-group in Israel, with description of a new species (Hymenoptera: Formicidae). 90894 records from CUMV Fish Collection (Arctos). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 2197 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 21 records from On the Lathrobium fauna of the Luoxiao Mountains, Central China. 23 records from A taxonomic revision of the kalshoveni species-group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae), with descriptions of six new species from Indonesia and Papua New Guinea. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 260 records from SuLaMa reptile survey II 2012. 6065 records from LISU Herbario Angola. 2770 records from Regeneración, crecimiento y dinámica poblacional del pino azul Pinus maximartinezii Rzedowski. 3953 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 14 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 864 records from Rhodolith Beds in Northern New Zealand: Characterisation of Associated Biodiversity. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 506500 records from Field Museum of Natural History (Zoology) Bird Collection. 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 1 records from A new African Apiocera species (Apioceridae, Diptera). 79 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 1861 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 352692 records from Plantae of Costa Rica (INBio). 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 12555 records from La Colección de Poliquetos (Annelida: Polychaeta) de la Facultad de Ciencias Biológicas, Universidad Autónoma de Nuevo León. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 35 records from A new species of Euricrium Enderlein from southern Brazil, new records for E. varians (Lane), a new combination, and a key for the Neotropical species of the genus. 5169 records from Fauna carcinológica de México. Crustáceos estomatópodos y decápodos del Golfo de México. Río Bravo, Tamaulipas a Cabo Catoche, Q.Roo. 30818 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 29540 records from Mycology herbarium, Tromsø Museum. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 131929 records from UAM Mammal Collection (Arctos). 10984 records from IZIKO: Marine Invertebrate Collection (1900-2011). 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 2 records from Pseudowuiessa, a new genus of brachypterous Mezirinae (Hemiptera: Heteroptera: Aradidae) from China. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 2481 records from HSU Wildlife Eggs and Nests. 2385 records from MATRIX project, Mabira in Uganda. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 31 records from New species of Macunahyphes Dias, Salles & Molineri (Ephemeroptera: Leptohyphidae), with taxonomic notes. 620 records from Digitalización de la colección FITO-UBIPRO, de las enfermedades y sus agentes causales, de los cultivos agrícolas de la región centro de México. 250 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco. 2 records from A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae). 77 records from Inhaltsstoffe_Blattmischproben_2008. 325 records from KU E16 Slæn - Tvinno. 158 records from Biodiversidad del Phyllum Mollusca asociada a las plataformas de explotación de gas natural (Campo Chuchupa: La Guajira, Colombia). 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 10 records from A new family, genus and species of freshwater amphipod Australomicroprotopus megacoxa gen. nov. sp. nov. (Senticaudata, Corophiidea, Microprotopoidea, Australomicroprotopidae fam. nov.) from Australia. 8 records from A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India. 1948 records from CCBER Mammalogy Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 3 records from Key for identification of Cladocera of the subfamily Aloninae (Anomopoda: Chydoridae) from South-East Asia. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 136 records from Plants galls. 4 records from Duocrassana longula, new genus and species of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae) from southern Mexico and its relationship to other genera in Athysanini. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 9 records from Cypridinid Ostracods. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 49358682 records from Artdata. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 171 records from Propuesta de categorías de riesgo para la ictiofauna dulceacuícola de Oaxaca. 464 records from Lepidoptera systematic collection, NTNU University Museum. 108824 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 1826 records from Collection des Mollusques (BOUM). 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 414 records from Jardín Botánico Carlos Thays. Colección de Nativas Vivas. 348269 records from Reef Life Survey: Global reef fish dataset. 22 records from Two new paratanaid Tanaidacea (Crustacea: Malacostraca: Peracarida) from the Hawaiian Islands, with illustrated taxonomic keys. 15 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 3304 records from Proyecto de cultivo extensivo y comercialización de las mariposas de la región de Chajul, Chiapas. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 13325 records from Herbier du Bénin. 6 records from MfN - Micropaleontology. 4 records from Beiträge zur Kenntnis der Spinnenfauna des Kt. Tessin III - Für die Schweiz neue und bemerkenswerte Spinnen (Arachnida: Araneae). 15 records from Clasificación de tres especies endémicas de Mammillaria dentro del PROY-NOM-ECOL-059-2000. 3 records from Loxosomella decorata n. sp., a new solitary entoproct from San Juan Island, WA, USA. 2577 records from Shellfish (WSHN-MS). 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 83733 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 9123 records from Flora of Słowiński National Park, Poland. 711 records from Odonata collection, NTNU University Museum. 1 records from Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific. 1 records from Hymenoptera: Eucoilinae (Cynipoidea). 1280 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 810036 records from Museum Victoria provider for OZCAM. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 3947 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 3769 records from Eggs Specimen. 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 27291 records from Butterflies of Ireland. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 49827 records from CRCM Vertebrate Collection. 31 records from Stalked jellyfishes (Cnidaria: Staurozoa) of South Africa, with the description of Calvadosia lewisi sp. nov.. 7 records from Anopheles prachongae, a new species of the Gigas Complex of subgenus Anopheles (Diptera: Culicidae) in Thailand, contrasted with known forms of the complex. 1463 records from Vertebrados terrestres de San Juan de Camarones, Durango. 216 records from VIP_data_topsoil_jointsampling_microbiolgroups_2008_Heiko_Nacke. 8 records from New genus of diminutive microhylid frogs from Papua New Guinea. 3 records from Diatom abundance of Hole 38-338, Part 2. 137 records from SNH Invertebrate Site Condition Monitoring 2013/14: Alvie SSSI. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8579 records from The atlas of breeding birds in Małopolska. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 71 records from (Data S1) Palynology of ODP Site 113-696. 17 records from New taxa and notes on some Landrevinae (Orthoptera: Gryllidae) from Malay Peninsula. 12681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb).. 31 records from Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini). 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 45 records from A taxonomic review of Korean Liogluta Thomson (Coleoptera, Staphylinidae, Aleocharinae) with descriptions of three new species. 18940 records from Cowan Tetrapod Collection - Mammals. 2955 records from Change in aboveground biomass carbon stock following the establishment of exclosures on degraded lands in Tigray, Ethiopia. 14673 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 341 records from Inventario y monitoreo de anfibios y mariposas en la Reserva de Calakmul, Campeche. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 2 records from A new species of Physomerus Burmeister (Hemiptera: Heteroptera: Coreidae: Coreinae), with a key to the species of India. 1942 records from Ecología poblacional y alimentaria del lobo marino de California en la Bahía de La Paz, BCS, Golfo de California. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 14502 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 19973 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 1534 records from Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1292 records from Census of tapia forest plant species in central highland of Madagascar. 6 records from Arthropoden aus südostalpinen Höhlen. 1803 records from Flora of tanzania. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 381 records from Priority effects of early successional insects influence late successional fungi in dead wood. 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 830 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 41001 records from Museu Paraense Emilio Goeldi - Mastozoology Collection. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 276513 records from MBM - Herbário do Museu Botânico Municipal. 314 records from Peces laguna El Tinije. 666 records from Vascular plants from a study of primary producer traits across an altitudinal gradient in alpine Finse. 1905 records from BioGIS - Reptiles - INPA database. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 777 records from INRA-Versailles Arabidopsis natural variants. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 62 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 12184 records from Diversidad de abejas (Hymenoptera: Apoidea) de la Reserva de la Biosfera El Triunfo, Chiapas. 13625 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 2412 records from Ohio University Invertebrate Paleontology Collection. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 13807 records from Flora de las playas y dunas costeras de México. 3 records from Odontotrypes (Odontotrupes) tawangensis new species (Coleoptera: Geotrupidae) from Arunachal Pradesh, India. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 2856 records from Alien macro-invertebrates in Flanders, Belgium. 1323 records from Algae (KBRC-AG). 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 73 records from The "Martian" flora: new collections of vascular plants, lichens, fungi, algae, and cyanobacteria from the Mars Desert Research Station, Utah. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 31 records from Coleção de Nemertea do Museu Nacional - UFRJ. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 17642 records from International Collection of Microorganisms from Plants (ICMP). 2243 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 91 records from European bison in Białowieża Primary Forest. 24 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 32 records from Ice Zooplankton Beaufort Sea. 3597 records from Harvestmen of French Guiana. 1322 records from PSUZC-Amphibians Collection. 2312 records from Abejas silvestres (Hymenoptera: Apoidea) de la región Praderas de Tokio-El Potosí - Sierra Mazmorras - Cañón de Iturbide, Coahuila y Nuevo León, México. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 246253 records from Waterbird census in Spain. 41758 records from USGS South Florida Fish and Invertebrate Assessment Network Fish. 10895 records from Stabbetorp - Floristiske registreringer 2016. 1 records from Nothrus canaliculatus. 2815 records from Helgeland Museum, Araneae. 6438 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 527 records from Inventaire floristique de Beza Mahafaly. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 8611 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 5 records from New species of Curculionichthys (Siluriformes: Loricariidae) from the eastern Guiana Shield. 8 records from New taxonomic, stratigraphic, and geographic information on the genus Faksephyllia Floris, 1972 (Scleractinia; Caryophylliidae); first records from the Oligocene of Austria, Germany, and Italy. 1495 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 82 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 28 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 5458 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 3 records from New Species of Woolly Lemur Avahi (Primates: Lemuriformes) in Bemaraha (Central Western Madagascar). 18571 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 3404 records from Lista florística de la Costa Grande del estado de Guerrero. 1664 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 625 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 22 records from Five new species and a new country record in American Cerambycidae (Coleoptera). 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 157 records from Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations. 20727 records from Arctic Species Trend Index (ASTI) : Terrestrial. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 3276500 records from Insecta of Costa Rica (INBio). 17 records from Sarcinoid green algae (Chlorophyta) of Algal Collection of Soil Science Institute (ACSSI). 17 records from ZUEC-NMA - Coleção de Nematoda do Museu de Zoologia da UNICAMP. 62015 records from Atlas of Iberian water beetles (ESACIB database). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 132 records from Fiocruz/CCAMP - Coleção de Campylobacter. 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 122 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 11392 records from Danish Plant Bugs (Miridae). 1298 records from Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 7 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 30769 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 1 records from Recharacterization of Rhinophis dorsimaculatus Deraniyagala, 1941 (Serpentes: Uropeltidae), including description of new material. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 25066 records from Mollusca Collection of the Museu Nacional/UFRJ. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2902 records from Bases para el monitoreo de dos especies de carnívoros medianos en la Reserva de la Biosfera de Mapimí, Durango. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 1495 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 8951 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 67 records from Early-diverging bumblebees from across the roof of the world: the high-mountain subgenus Mendacibombus revised from species’ gene coalescents and morphology (Hymenoptera, Apidae). 906 records from Digital Florula - Las Cruces Biological Station. 2172 records from Colección de Reptiles. 24121 records from Endemic plants of the Congo basin. 32 records from Braconid wasps of subfamily Alysiinae (Hymenoptera: Braconidae) as endoparasitoids of Selachops flavocinctus Wahlberg, 1844 (Diptera: Agromyzidae) in the Central Urals, Russia. 18 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 2 records from Zobellia amurskyensis sp. nov., Zobellia laminariae sp. nov. and Zobellia russellii sp. nov., novel marine bacteria of the family Flavobacteriaceae. 3 records from Collection Crustacea - ZSRO. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 158 records from Distribución actual, estatus poblacional y evaluación del estatus de protección del pavo ocelado (Agriocharis ocellata). 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 119 records from Various insect orders, NEF. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 1 records from SDSM Botany and Paleobotany Collections. 23562 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from Celaeno spinosa. 11762 records from Chrysomelidae of the Carpathians. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 1510 records from Collection botanique Jaubert et Saul (BOUM). 2 records from Event-based biogeography of Eusarcus dandara sp. nov. (Opiliones: Gonyleptidae), an endemic species of the Northern Atlantic Rainforest of Brazil, and its closely related species. 4 records from Out of the South? The first Afrotropical record of Prochyliza Walker (Diptera: Piophilidae), with description of a new species. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 934 records from GenLink - Collected plant samples on grassland EPs. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 1 records from On the Chilopoda from Turkey. 1 records from On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.]. 1728 records from CASES: The pre-winter assemblages of southeastern Beaufort Sea. 5 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 882456 records from SA Fauna (BDBSA). 13 records from A new species of Eigenmannia Jordan and Evermann (Gymnotiformes: Sternopygidae) from the upper rio Paraguai basin. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 15953 records from Algae (S). 23 records from Descriptions of larvae of four species of Hydropsyche (Hydropsychidae: Trichoptera) from Thailand. 1652 records from Depletion fishing in the rivers Grote Nete and Kleine Nete in Flanders, Belgium. 1809 records from BenthosChukchiFN762_1976_Falk5. 26017 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 3 records from First record of order Embioptera (Insecta) for the State of Tocantins, Brazil, with description of a new species of Clothoda Enderlein. 10255 records from Araneae Collection. 10 records from First report of some known Trichodinella epizootica Šramek-Hušek, 1953, and Tripartiella Lom, 1959 from the cultured Oranda Gold Fish (Carassius auratus auratus) in India. 1231 records from Registros faunísticos de invertebrados marinos en el SE del Golfo de California. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 80 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 3535 records from Biología poblacional de Isostichopus fuscus (Ludwig, 1875) (Echinodermata: Holothuroidea) en el sur del Golfo de California. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 272 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 16568 records from Fungus herbarium, UiB. 678 records from NCC Berkshire Chalk Grassland Survey 1985. 118601 records from BMSM Bailey-Matthews National Shell Museum. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 2957 records from HSU Wildlife Mammals. 146809 records from OHN. 411 records from SuLaMa reptile survey I 2012. 6000 records from Algas marinas bentónicas de la Península de Yucatán y uso potencial de especies selectas. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 28954 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 30 records from Specimens from India at the University Museum at the University of Bergen. 196142 records from Field Museum of Natural History (Zoology) Mammal Collection. 25 records from Cerdos asilvestrados (Sus scrofa) en la Reserva de la Biosfera Sierra La Laguna: Evaluación e impacto sobre la biodiversidad. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 21672 records from TPWD HARC Texas Coastal Fisheries, Corpus Christi Bay Gill Net. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 16 records from Bolivian Mimosa (Leguminosae, Mimosoideae): three new species and a species checklist. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 1129 records from Upper Silesian Museum, Insect Collection. 378 records from Ichthyologie ZMK. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1 records from Cesiribacter roseus sp. nov., a pink-pigmented bacterium isolated from desert sand. 657 records from MVZ Hildebrand Collection (Arctos). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 19 records from The Dixa inextricata Dyar & Shannon (Diptera: Dixidae) species group, with two new cryptic species from the eastern Nearctic Region. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 1 records from Oribates angulatus. 51 records from Packer Collection / Xenochilicola bees, Chile. 1626 records from Ornithologie ZMK. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 172036 records from Lund Museum of Zoology (MZLU). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 9 records from Revision of the non-Afrotropical species of Trigastrotheca Cameron (Hymenoptera: Braconidae: Braconinae) with descriptions of four new species. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 8 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 1052 records from Migración, movimiento y distribución estacional del cachalote en el Golfo de California. 1 records from Protozoa ZMK. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 281 records from Myriapoda of Costa Rica (INBio). 568 records from Expedición Providencia I - INVEMAR. 307 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 2 records from Amphibia ZMK. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 637198 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 637398 records from Données ONF Faune-Flore-Fonge. 1 records from Nothrus bispinosus. 7 records from Vermes ZMK. 1 records from Oribates badius. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 38 records from Revision of the Taiwanese species of the genus Leptophion Cameron, 1901 (Hymenoptera: Ichneumonidae: Ophioninae), with a discussion of their phenology and distribution. 1 records from Ctenophora ZMK. 898 records from kyklades. 1 records from Nothrus bicarinatus. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 382 records from Reptilia ZMK. 137 records from SNH Invertebrate Site Condition Monitoring 2013/14: North Rothiemurchus Pinewood SSSI. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 39 records from Arachnologie ZMK. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 2 records from A new species of the genus Paracypria (Crustacea: Ostracoda: Cypridoidea) from the Fiji Islands. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 48 records from First description of the sexuals of Camponotus opaciventris Mayr, 1879 (Hymenoptera, Formicidae), with notes on distribution in Western Himalaya. 2 records from Bryozoa ZMK. 8 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 27 records from Root Length and Mass VIP 2008 Rillig. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 20992 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 6588 records from FCAB - Herbário Friburguense. 1265 records from Crustacea ZMK. 27290 records from Bird Monitoring Data. 104 records from Mammalogie ZMK. 2 records from REDESCRIPTION OF TETRAMORIUM ATLANTE CAGNIANT, 1970, NEW STATUS (HYMENOPTERA: FORMICIDAE: MYRMICINAE). 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 4 records from Tunicata ZMK. 2 records from Two new species within the genus Seira Lubbock, 1869 from Morocco (Collembola, Entomobryidae). 32109 records from Herbier de Nouvelle-Calédonie. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 3 records from Pantopoda SMF. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 68 records from Malakologie ZMK. 2179 records from Base de datos y colección de anfípodos (Hyperiidea:Crustacea) de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 61 records from ZUEC-PLA - Coleção de Platyhelmintes do Museu de Zoologia da UNICAMP. 733 records from Catalogue of the family Ologamasidae Ryke (Acari: Mesostigmata). 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 10 records from Cnidaria ZMK. 10 records from New Zopheridae (Coleoptera: Tenebrionoidea) from Baltic amber. 165299 records from CAS Invertebrate Zoology (IZ). 16 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 6796 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 29 records from Tortugas marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 4 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 3 records from Three new species of the subgenus Ashima (Diptera: Drosophildae: Phortica) from southwestern China, with DNA barcoding information. 2 records from Porifera ZMK. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 17 records from Abyssal fauna of the UK-1 polymetallic nodule exploration area, Clarion-Clipperton Zone, central Pacific Ocean: Cnidaria. 13 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 16621 records from Crustacea collection of National Museum of Nature and Science. 12 records from Echinodermata ZMK. 90 records from Relascope sum of Sitka spruce Picea sitchensis in Fusa and Tysnes. 2 records from Phylogenetic relationships and a new classification of the family Cyclopteridae (Perciformes: Cottoidei). 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 1111 records from La ballena jorobada, Megaptera novaeangliae, en la Península de Baja California Sur, México. 45697 records from Archives of the Arctic Seas Zooplankton. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 2054 records from Status, ecología y conservación de loros Amazona en el Noreste de México. 7 records from A review of Japanese species of Allophrys Förster (Hymenoptera: Ichneumonidae: Tersilochinae). 9 records from Diagnosis of Calagasma Bergroth and Epipedus Spinola with description of Calagasma eclipsa sp. nov. and Epipedus rolstoni sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 476 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 1 records from On centipedes (Chilopoda) of Albania, 2. 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 7 records from A new species of Anacroneuria Klapálek 1909 (Plecoptera: Perlidae) from Espírito Santo State, southeastern Brazil and comments on additional species. 51511 records from IMOS - AusCPR: Zooplankton Abundance. 2 records from Endogean and cavernicolous beetles of the Balkans. XVI. A new, anophthalmous species of Neuraphes Thomson, 1859 (Coleoptera: Staphylinidae: Scydmaeninae) from Albania. 1029 records from Freshwater plants of Cameroon. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 418564 records from BLS Lichen Database: English churchyards. 1 records from On the Chilopoda from Turkey. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 7697 records from MBML-Aves - Coleção de Aves MBML. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 38 records from Harant H. 1939. Les fonds de peche pres d'Alexandrie. Ascidiacea (Cartes 1-5). Notes et Memoirs No 28. Institut fouad 1er d' Hydrobiologie et de peche, Egypt. 287 records from The Sea Ice Fauna of Frobisher Bay, Arctic Canada 1981 and 1982. 41 records from The genus Leucophenga (Diptera, Drosophilidae), part VI: the argentata species group from the East Asia, with morphological and molecular evidence. 61 records from Shrews of Poland. 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 940 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 4 records from Uncovering the diversity of the neotropical genus Elaphopsocus (‘ Psocoptera’: Psocidae: Amphigerontiinae): from one to ten species. 4 records from New country records of reptiles from Laos. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 89 records from Collection Crustacea - PUM. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 34 records from Faunistic studies of the tribe Brachinini (Carabidae: Coleoptera) from northern Pakistan. 490 records from flower availability 2007 Schwäbische Alb. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 48000 records from Tallinn Botanic Garden. 14420 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Foraminifera National Collection (MACNFo). 7113 records from Primera fase de actualización de la Colección de Siphonaptera Alfredo Barrera del Museo de Zoología Alfonso Herrera. 5 records from Indopamphantus makutaensis, a new genus and species, and Indopamphantini, a new tribe of Pamphantinae (Hemiptera: Heteroptera: Geocoridae), as the first representative of the subfamily from the Oriental Region. 1 records from Nothrus convexus. 5 records from Redescription of two European species of Acerentomidae (Protura) belonging to the Italian fauna. 2032 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 200 records from Zoological collection of the National Museum. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 103 records from A revision of the genus Andesipolis (Hymenoptera: Braconidae: Mesostoinae) and redefinition of the subfamily Mesostoinae. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2864 records from Creación de la base de datos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, y de la reserva de la biosfera Islas del Golfo de California para el grupo de los mamíferos. 102 records from A Lichen Survey of the Ben Nevis Plateau. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 2095 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 1271 records from Fiocruz/CCGB - Coleção de Culturas do Gênero Bacillus e Gêneros Correlatos. 9 records from Chenopodium vulvaria. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 2231 records from UCM Bird Eggs/Nests Collection (Arctos). 11251 records from Herbarium areqvipense (HUSA). 21134 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 1848 records from NCSM PaleoBotany Collection. 75 records from Conocimiento de la diversidad y distribución actual del maíz nat
Keywords: GBIF; biodiversity; species occurrences